Constructivism Philosophy in Developing Prospective Educators on the Implementation of Merdeka Belajar in Vocational Schools: ENGLISH - Ichsan, Ichsan; Arif Saefudin; Fitria Meisarah (Cita konsultindo, 2023)
The development of the business world and the industrial world demands more hard skills, creativity and critical thinking from school graduates, including vocational school graduates. One of the efforts to achieve this is by implementing a Merdeka curriculum, where the learning process is constructivism, which means student-centred learning. For this reason, a prospective educator's understanding of the constructivism philosophy contained in the independent learning concept must be improved first. This article will explain the philosophy of constructivism in the concept of independent learning to develop the understanding of prospective educators so they can implement it in learning at vocational schools. The author uses the library research method to explore and collect relevant information and data from various sources. Constructivism is defined as learning that emphasises that knowledge is the formation (construction) of oneself. Constructivism emphasises the process rather than the result and has the principle of student centre learning, the teacher is only a facilitator, and students discover more on their own. This is very much in line with independent learning; students can determine the knowledge they need by emphasising the learning process. Prospective educators have an important role in building the competencies needed by students; these competencies are the 4C abilities (critical thinking, communication, collaboration, and creativity). Education that applies the 4C skills and gives the freedom to think critically will form learners with superior and adaptive characteristics.